Total Colonic Aganglionosis: A 15-Year Single Center Experience - Blackburn, Simon; Corbett, Phillip; Griffiths, D. Mervyn; Burge, David; Beattie, R. Mark; Stanton, Michael (European Journal of Pediatric Surgery, 2014)
Purpose Total colonic aganglionosis (TCA) is a rare condition, which is challenging to manage. Outcome data are sparse. We aimed to review the demographics, treatment, and outcomes of TCA in our center.Patients and Methods A retrospective case note review of 15 years from a single center was undertaken.Results A total of nine patients (five male) were managed. Gestational age at birth was 39 weeks (range, 32.5–41 weeks). All patients were referred with distal intestinal obstruction at a median of day 2 (range, 1–6 days) of life. Two patients were managed with a long-term stoma. One died with persistent functional obstruction (despite a ganglionic stoma). Of the nine patients, seven patients underwent staged pull-through: three Soave, three Duhamel, and one Martin procedure with no short-term complications. All patients had at least one readmission with enterocolitis, diarrhea, or high stoma output. Further procedures were required in four of the seven patients. Only one child (older than 3 years) has achieved continence. Two children (both aged 8 years) requested reformation of a stoma to manage incontinence.Conclusion In this series, we observed high morbidity and poor functional outcome, which should be anticipated in TCA. Patients with TCA have a high probability of requiring a long-term stoma and this should be considered as a management option.
Keywords: Hirschsprung disease; Total colonic aganglionosis; surgery; pediatric; child